(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Influenza and acute respiratory viral infections (ARVIs) represent among the most significant recurring public health challenges worldwide, imposing substantial morbidity, mortality, and socioeconomic burden on populations across all income settings. Worldwide, annual seasonal influenza affects up to 1 billion people and causes 3-5 million severe cases and up to 650,000 deaths related to respiratory causes. The seasonal nature of these infections - driven by a convergence of environmental, virological, and behavioral factors - follows predictable yet complex patterns that vary by hemisphere, climate zone, pathogen type, and host population. This article provides a comprehensive, evidence-based review of the seasonal epidemiology of influenza and ARVI, examining the environmental and immunological mechanisms underlying seasonal peaks, the comparative epidemiology of major respiratory viruses, patterns in high-risk populations, and current evidence on vaccination and antiviral prophylaxis as control measures. Understanding these patterns is foundational to designing effective surveillance systems and preventive strategies.